The Female Athlete Triad: An Assessment of Current Practices in Primary Care and Benefit of Educational Intervention - Brewington, Dana; Johnson, Derrick; Stovak, Mark; Harvey, AT (Kansas Journal of Medicine, 2012)
Background. The Female Athlete Triad (Triad) is characterized by negative energy balance, disordered menstrual cycles, and low bone mineral density. The understanding and practices of primary care physicians (PCPs) regarding the Triad and the benefit of an educational intervention were assessed. Methods. PCPs attending a regional conference were surveyed prior to, immediately after, and three months following the plenary lecture on the Triad. Surveys included knowledge about the components, diagnostics, treatment, clinician practice, and comfort level with regard to the Triad. Results. The pre-test survey was completed by 84 of 126 (67%) attendees. The lecture increased from 53% to 98% the proportion of PCPs who identified the three domains of the Triad. Knowledge scores improved over the course of the lecture (from 3.4 to 5.1, p < 0.05), particularly regarding Triad components (effect size = 1.2) and treatment (effect size = 1.6) with only small gains in diagnostic knowledge (effect size = 0.1 to 0.3). The three-month follow-up survey, completed by only seven clinicians (8%), suggested good retention of knowledge though little practice changes. Conclusions. A 50-minute educational session improved knowledge about the Triad. Particular improvement was noted in understanding the underlying etiology and treatment.